2012
DOI: 10.1029/2011jd016360
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon emissions characterization in the Colorado Front Range: A pilot study

Abstract: The multispecies analysis of daily air samples collected at the NOAA Boulder Atmospheric Observatory (BAO) in Weld County in northeastern Colorado since 2007 shows highly correlated alkane enhancements caused by a regionally distributed mix of sources in the Denver‐Julesburg Basin. To further characterize the emissions of methane and non‐methane hydrocarbons (propane, n‐butane, i‐pentane, n‐pentane and benzene) around BAO, a pilot study involving automobile‐based surveys was carried out during the summer of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
530
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 404 publications
(567 citation statements)
references
References 29 publications
29
530
8
Order By: Relevance
“…The diurnal patterns of benzene/ethylbenzene and toluene/ethylbenzene in this study (Fig. 9b,d) was opposite to that observed in Dallas, which was mainly influenced by vehicle emission (Qin et al, 2007). After 14:00 LT, the increasing of the ratios and aromatic concentrations were due to the weakening of photochemical activities.…”
Section: Ambient Ratios: Sources and Photochemical Removalcontrasting
confidence: 37%
“…The diurnal patterns of benzene/ethylbenzene and toluene/ethylbenzene in this study (Fig. 9b,d) was opposite to that observed in Dallas, which was mainly influenced by vehicle emission (Qin et al, 2007). After 14:00 LT, the increasing of the ratios and aromatic concentrations were due to the weakening of photochemical activities.…”
Section: Ambient Ratios: Sources and Photochemical Removalcontrasting
confidence: 37%
“…As a result of these challenges, validation of VOC emission reports is only occasionally conducted. The alternative has been evaluations of VOC emissions using emission ratios in ambient air (17)(18)(19)(20)(21)(22)(23)(24). In this paper, a unique methodology is shown that provides validation of VOC emission reports using a top-down approach, which allows emission rates for a large number of VOCs and chemical speciation profiles from each oil sands surface mining facility to be determined.…”
Section: Significancementioning
confidence: 99%
“…These studies also identified three possible mechanisms for explaining this relationship, and concluded that the most likely of these is subsurface migration from leaking gas wells. Other researchers have observed thermogenic and other subsurface-sourced methane in atmospheric concentrations high above background levels near conventional and unconventional gas development (4)(5)(6), suggesting that leaking wells may also contribute to fugitive methane and other associated gas emissions, with clear climatic and air quality consequences (7).…”
mentioning
confidence: 99%